Solving Landau Kinetic Equation of quantum Liquid diffusion coefficients of optical waves depending on temperature. - Mizam, Mohey Aldin (Latakia University Journal -Basic Sciences Series, 2018)
The theory of quantum liquids (quantum liquid theory) in the last few Years largely developed because of the brood spectrum of natural phenomenon relating to the limitation of parameters of the this (the parameters of the Landau Fermi liquid theory). We aim through this paper to resolve kinetic equation for the spin density. After adding Rashba term of spin-orbit coupling that belong to Landau parameters of orders (). Also calculated the magnetic susceptibility also taking into account the mutual influence function,wich we have greeted from the collective perturbation energy. The propagation in quantum liquids by calculation(wave modes) at zeros complex function of magnetic susceptibility.